PENGARUH KONSUMSI REBUSAN DAUN SELEDRI (APIUM GRAVEOLENS) TERHADAP PENURUNAN TEKANAN DARAH PADAX LANSIA PENDERITA HIPERTENSI DI PANTI JOMPO YAYASANX GUNA BUDI BAKTI MEDAN TAHUN 2021 - Agusdarman Waruwu; Ayu Sartika Br. Sibagariang; Dedi Utomo Laia; Gustina Hulu; Tiarnida Nababan (STIKes Al-Insyirah Pekanbaru, 2021)
Into day's world, nearly 1 billion people have high blood pressure and itwill continue to increase every year. Hypertension isacondition in which aperson hasagradual increase in blood pressure in the blood vessels. Pharmacological management using drugs, while non-pharmacological suchas celeryleafdecoction. The purpose of this study was to determine the effect of consumption of celery leaf stew (apium graveolens) on reducing blood pressure inelderly people with hypertension at the Guna Budi Bakti Nursing Homei n 2021. This type ofresearchwas pre-experimental using a one-group pre-test and post-test plan.The test design is that the subject is observed before and after the intervention is carried out (Sugiyono,2018). The p-value test valueis x0.000<0.05, so it meansthat Hoisrejected.The conclusionisthat thereisan effect of consumption of celery leaf decoction (apium graveolens) on reducing blood pressure in elderly people with hypertension at the Guna Budi Bakti nursing home foundationin Medan in 2021. It is hoped that thisre search can util izenaturalin gredients.l ike celery leaves to control blood pressure to keep it normal.